The distance between us - West, Kasie (2013)
"Seventeen-year-old Caymen Meyers knows better thant to trust a rich boy. But then she meets the richest guy of all, who proves money might not matter after all"--Provided by publisher.
Keywords: Dating (Social customs) -- Fiction; Wealth -- Fiction; Single-parent families -- Fiction; Mothers and daughters -- Fiction; Young adult fiction